2021
DOI: 10.1038/s41598-021-90980-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress and cortisol stress reactivity predict breast milk composition

Abstract: We studied a sample of 146 Polish, exclusively breastfeeding mothers and their healthy born on time infants to explore the effect of perinatal psychosocial stress on breast milk composition. Maternal perinatal stress was assessed using Recent Life Changes Questionnaire summarizing stressful events from the previous six months. Stress reactivity was determined by administering the cold pressor test and measuring cortisol in saliva samples taken during the test. Breast milk sample was taken to measure energy, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 59 publications
1
45
0
1
Order By: Relevance
“…In a recent study, perinatal psychosocial stress (the intensity and number of maternal stressor) was negatively associated with FAs concentration and energy density of HM, while stress reactivity (cortisol measured in saliva taken during the cold pressor test) associated positively with fat and FAs and negatively with lactose. 47 The HM immune factors though were not affected by natural variations in maternal distress (questionnaires for stress, anxiety and depressive symptoms). 49 The level of cortisol in the amniotic fluid has been shown to be inversely correlated with infant cognitive development.…”
Section: S Tre Ssmentioning
confidence: 94%
See 3 more Smart Citations
“…In a recent study, perinatal psychosocial stress (the intensity and number of maternal stressor) was negatively associated with FAs concentration and energy density of HM, while stress reactivity (cortisol measured in saliva taken during the cold pressor test) associated positively with fat and FAs and negatively with lactose. 47 The HM immune factors though were not affected by natural variations in maternal distress (questionnaires for stress, anxiety and depressive symptoms). 49 The level of cortisol in the amniotic fluid has been shown to be inversely correlated with infant cognitive development.…”
Section: S Tre Ssmentioning
confidence: 94%
“…A short period of anxiety (acute stress), such as during infant hospitalisation, does not seem to affect HM macronutrient content, 48 whereas long‐term (chronic) stress results in the cumulative glucocorticoid burden and is associated with maternal diet and BC changes, thus may lead to HM composition changes. In a recent study, perinatal psychosocial stress (the intensity and number of maternal stressor) was negatively associated with FAs concentration and energy density of HM, while stress reactivity (cortisol measured in saliva taken during the cold pressor test) associated positively with fat and FAs and negatively with lactose 47 . The HM immune factors though were not affected by natural variations in maternal distress (questionnaires for stress, anxiety and depressive symptoms) 49 …”
Section: Stressmentioning
confidence: 97%
See 2 more Smart Citations
“…This is in addition to reducing milk vitamin and mineral content (Smit et al, 2000;Spring et al, 1985;Sauerwald et al, 2001). However, even non-disastrous contexts such as psychosocial stress negatively correlates with maternal milk fat and energy content (Ziomkiewicz et al, 2021) and mothers who reported higher levels of perceived stress exhibited significantly lower levels of milk immunoglobulin A (Moirasgenti et al, 2019;Groer et al, 2004). Stress arising from perinatal anxiety and depression can also be associated with significant differences in milk composition, including a reduction in DHA, increased sodium, and increased transforming growth factor β-2 (reviewed in Di Benedetto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%